The Influence of Organizational Culture on Employee Performance with Organizational Commitment as a Mediation Variable in the BIF Mantrijeronan Yogyakarta Cooperative - Teti Safari; Heri Usodo; R.A Marlien; M. Zaki Mubarok (LP2M IAIN Palopo, 2026)
The abstract contains a brief description of the purpose: describes the objectives and hypotheses of the research. Methods: describes the essential features of the research design, data, and analysis. It may include the sample size, geographic location, demographics, variables, controls, conditions, tests, descriptions of research design, details of sampling techniques, and data gathering procedures. Results: describes the key findings of the study, including experimental, correlational, or theoretical results. It may also provide a brief explanation of the results. Implications: show how the results connect to policy and practice and provide suggestions for follow-up, future studies, or further analysis.